ENHANCING STUDENTSâ LISTENING PROFICIENCY THROUGH THE INSTRUCTION OF (META)-COGNITIVE LISTENING STRATEGY - Mulyadi, Dodi (Getsempena English Education Journal, 2018)
AbstractMetacognitive listening strategy instruction is fruitful to enhance studentsâ autonomy by planning and deciding what the best strategy in mastering listening skills is. Meanwhile, the cognitive strategy instruction facilitates students to find out the solution to their listening problems. The study aimed to find out the effectiveness of (Meta)-cognitive listening strategy (M-CLS) instruction by administering the integrated listening strategy instruction between metacognitive and cognitive strategies on studentsâ listening proficiency. The participants were 38 EFL students of Universitas Muhammadiyah Semarang that consist of 20 for the experimental group and 18 for the control one. The M-CLS instruction that utilized the three stages including planning, monitoring, and evaluating stage was administered in experimental group for ten meetings. The quasi-experimental design was conducted to investigate quantitative data. The data were gathered by using a listening proficiency test adopted from TOEFL listening section. The descriptive statistics, Generalized Linear Model, and Paired Sample t-test reveal that the students in the experimental group achieve a higher score of listening proficiency with a significant achievement than those in the control group.Â Keywords: (Meta)-Cognitive Listening Strategy (M-CLS), Listening Proficiency,Â Â Â  Experimental Design, TOEFL, EFL Student Teachers